The Strategy Using Audio-Lingual Method in the Era Digital 4.0 to Accelerate English Speaking Skill Ability - Fidinillah, Mildan A.; Hampu, La Ode (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2025)
The objective of this study is to describe of the effect using audio lingual method toward students’ English speaking skill ability. This study using Quantitative approach that used hypothesis process, field observation, data analysis, and conclusion. Using this method supposes to the origin of the effect of variable audio lingual method (X) toward variable speaking English skill (y). The finding of this study was there was a significant effect of using audio lingual method toward students English speaking skill ability at grade VIII SMP 3 Cibinong. T test show that ????counting was 4,301 and score ???????????????????????? was 1,724 with significance α = 0,05 and dk 19, it meams that ????0 was reject and ????1 was accepted. The hypothesis; there was effect of using Audio lingual method toward students speaking English ability at grade VIII SMPN 3 Cibinong was accepted